Development of a semi selective medium for isolation of Xanthomonas campestris pv. musacearum from banana plants - Tripathi, L.; Tripathi, J.N.; Tushemereirwe, Wilberforce K.; Bandyopadhyay, Ranajit (Springer, 2007)
Banana Xanthomonas wilt, caused by Xanthomonas campestris pv. musacearum, is a new threat to banana cultivation in eastern Africa. The causal bacterium grows slowly in culture and is easily overgrown by contaminants. A selective culture medium for isolation of X. c. pv. musacearum will facilitate disease study. A medium that suppressed saprophytic growth and possessed diagnostic characters for the pathogen was developed. Various carbon sources were tested with two isolates of X. c. pv. musacearum, and sucrose was selected as main carbon source. The susceptibility of X. c. pv. musacearum and other bacterial strains was tested with 29 different antibiotics. Cephalexin and cycloheximide had no effect on X. c. pv. musacearum but cephalexin inhibited most of the saprophytes and cycloheximide inhibited the fungal contaminants. Based on these studies, we have developed a semi-selective medium YTSA-CC containing yeast extract (1%), tryptone (1%), sucrose (1%), agar (1.5%), cephalexin (50 mg l−1) and cycloheximide (150 mg l−1), pH 7.0. The pathogen X. c. pv. musacearum was easily identified as yellowish, mucoid and circular colonies on YTSA-CC medium. This simple semi-selective medium was effective for isolation of X. c. pv. musacearum from infected banana tissues and soil, and it should be a valuable tool in ecological and epidemiological studies.